2004
DOI: 10.1093/tropej/50.6.354
|View full text |Cite
|
Sign up to set email alerts
|

Plesiomonas shigelloides-associated Diarrhoea in Bangladeshi Children: A Hospital-based Surveillance Study

Abstract: Little is known about clinical and epidemiological features of Plesiomonas shigelloides-associated diarrhoea in children. We reviewed hospital-based surveillance records of 38 children with diarrhoea having P. shigelloides as the only pathogen isolated from their faecal specimen. Of those 38 children, 29 (76 per cent) were below 2 years of age and 28 (74 per cent) were male. Thirty-two (84 per cent) children presented with watery diarrhoea and six (16 per cent) had dysenteric stools. Vomiting was a feature in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Shigellosis due to S. sonnei is reported to occur at low rates among people living in developing countries. Plesiomonas shigelloides is a gram-negative bacteria often found in surface water that shares antigens with S. sonnei , and until recently P. shigelloides has been a frequently isolated enteric pathogen from <2 years old Bangladeshi children in the diarrhea hospital [15], [16]. It is well accepted that exposure to P shigelloides, through contaminated drinking water, may immunize people to S. sonnei in these developing countries [17].…”
Section: Discussionmentioning
confidence: 99%
“…Shigellosis due to S. sonnei is reported to occur at low rates among people living in developing countries. Plesiomonas shigelloides is a gram-negative bacteria often found in surface water that shares antigens with S. sonnei , and until recently P. shigelloides has been a frequently isolated enteric pathogen from <2 years old Bangladeshi children in the diarrhea hospital [15], [16]. It is well accepted that exposure to P shigelloides, through contaminated drinking water, may immunize people to S. sonnei in these developing countries [17].…”
Section: Discussionmentioning
confidence: 99%
“…Most infections are characterized by self-limiting diarrhea with blood or mucus, abdominal cramps, vomiting, and fever (130). While most diarrheal episodes are described as acute, there have been reported chronic cases lasting over 2 weeks (135).…”
Section: Plesiomonas Shigelloidesmentioning
confidence: 99%
“…Interestingly, stools samples as an end product of nutrients metabolism in the content section, several potential aquatic pathogenic bacteria were enriched, including Serratia, Acinetobacter johnsonii, Plesiomonas shigelloides, and Aeromonadaceae (González et al, 2000;Martins et al, 2013;Nadirah et al, 2012;Huang et al, 2018). P. shigelloides is a cause of diarrhea in human, usually isolated from the faeces (Khan et al, 2004) and has also been found from the gut of many fishes, such as tilapia (Oreochromis niloticus) (Nadirah et al, 2012), largemouth bass Micropterus salmoides (Larsen et al, 2014) and Japanese eel Anguilla japonica (Hsu et al, 2018). In grass carps, P. shigelloides has also been found to be associated with muscle erosive disease (Hu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%